Experimental investigation of phase equilibria in the Al–Cr–Fe system. (September 2019) - Rank, Maximilian; Franke, Peter; Hoffmann, Jan; Seifert, Hans J.
Abstract: The literature of the ternary Al–Cr–Fe system was evaluated and major open questions were identified. Transition temperatures between α-Fe, Al (A2) – FeAl (B2) and FeAl (B2) – Fe3 Al (D03 ) as well as solidus/liquidus temperatures in the Cr-rich corner were determined. The results from thermal analysis show a substantial decrease of the A2/B2 transition temperature with increasing Cr content at constant x(Al). Furthermore, a partial solidus and liquidus projection below 50 at.-% Al were created. Several partial isothermal sections have been studied with equilibrated alloys and diffusion couples. Therefore, complementary methods were used such as thermal analysis, electron microscopy, chemical analysis, X-ray powder diffraction and electron probe microanalysis. Equilibration experiments have been performed at 973 K, 1173 K, 1315 K, 1373 K and 1423 K and two partial isothermal sections at the two lowest temperatures were constructed indicating a solubility of 22 at.-% iron in the AlCr2 phase at 973 K. Highlights: A2/B2 transition temperatures decrease with increasing x(Cr) at constant x(Al). Liquidus and solidus projection below 50 at.-% of Al. Good agreement between diffusion couples and equilibration annealing. Partial isothermal sections at 973 K and 1173 K. Solubility of Fe in AlCr2 at 973 K was found to be ∼ 22 at.-%.